Cooperative influences of nanoparticle localization and phase coarsening on thermal conductivity of polypropylene/polyolefin elastomer blends. (November 2019) - Zhang, Xi; Wada, Toru; Chammingkwan, Patchanee; Thakur, Ashutosh; Taniike, Toshiaki
Graphical abstract: Abstract: Polypropylene (PP)/polyolefin elastomer (POE)/aluminum oxide (Al2 O3 ) nanocomposites were prepared based on a reactor granule technology (RGT). The effect of nanoparticle migration and phase morphology evolution on the formation of thermal conductive networks was systematically studied. The utilization of RGT and POE with high viscosity enabled successful migration of in-situ generated Al2 O3 nanoparticles at the interface of PP and POE, as combined results of uniform dispersion of Al2 O3 and accompanied small phase domain size of PP [1] . The localization of the nanoparticles at the interface also contributed to suppression of the phase coarsening during annealing. The nanoparticle migration to the interface and the retarded phase coarsening synergistically contributed to the enhanced thermal conductivity.